(untitled) (Historia, 2022)
White maize sadza is the most eaten food in Zimbabwe. Yet, over the decade of the 2000s, its consumption was threatened by drought and consequent acute food shortages. Small grains – sorghum and millet – offered a panacea to looming starvation and civil unrest. Yet, as we argue in this article, its access became rooted increasingly within political contestations between the ruling ZANU PF government, the budding opposition party and ordinary citizens. Using the story of small grains – sorghum and millet – between 2000 and 2010, we trace how food (in)security took a political form, stirring a pot of sometimes violent clashes between political and social contenders. We argue that through ‘political grain’, various political and social elites were able to amass wealth and power for themselves and grab control of sociopolitical discourse on food security during the crisis years. As the state imposed a series of seemingly well-intentioned and sometimes even widely welcomed food initiatives such as Operation Maguta and BACOSSI, these food security measures were often ad hoc, temporary and – as we argue – actually had an adverse long-term impact on local grain production and food availability. The government worked through key parastatals like the Grain Marketing Board and the Reserve Bank of Zimbabwe to allocate resources and food support to ruling party loyalists. In this period, the ZANU PF regime was concerned primarily with holding on to its waning political power and avenues for personal wealth accumulation at the expense of food security in the country. This paper demonstrates how an anthropogenically-induced ‘hunger’ effectively prolonged ZANU PF’s control of society – but we also show how ‘small people’ fought back against President Robert Mugabe’s ‘big men’ by embracing the growing and eating of traditional ‘small grains’. Opsomming Witmielie-sadza is die stapelvoedsel van die meeste mense in Zimbabwe. Tog, oor die dekade van die 2000s, is die verbruik daarvan deur droogte bedreig met gevolglike akute voedseltekorte. Kleingrane – sorghum en rapoko – het uitkoms vir dreigende hongersnood en burgerlike onrus gebied. Maar soos in hierdie artikel geargumenteer word, het die toegang tot kleingrane toenemend verstrengel geraak in `n politieke stryd tussen die regerende ZANU PF-regering, die ontluikende opposisieparty en gewone burgers. Ons gebruik die verhaal van kleingrane tussen 2000 en 2010 om aan te toon hoe voedsel-(on)sekerheid ’n politieke vorm aangeneem het, wat gewelddadige botsings tussen politieke en sosiale aanspraakmakers / mededingers aangestig het. Ons argumenteer dat verskeie politieke en sosiale elites in staat was om rykdom en mag te bekom en beheer oor die sosio-politieke diskoers rondom voedselsekerheid tydens die krisisjare uit te oefen. Hoewel die staat ’n reeks oënskynlik goedbedoelde en soms selfs populêre voedselinisiatiewe soos Operasie Maguta en BACOSSI ingestel het, was hierdie voedselsekerheidsmaatreëls dikwels ad hoc, tydelik en het ironies genoeg ’n nadelige langtermyn-impak op plaaslike graanproduksie en voedselbeskikbaarheid gehad. Die regering het deur belangrike semi-staatsinstellings soos die Graanbemarkingsraad en die Reserwebank van Zimbabwe gewerk om hulpbronne en voedselondersteuning aan regerende partylojaliste toe te ken. In hierdie tydperk was die ZANU PF-regime hoofsaaklik gefokus op die behoud van sy kwynende politieke mag en manière vir persoonlike verryking ten koste van voedselsekerheid in die land. Hierdie artikel demonstreer hoe ’n antropogenies-geïnduseerde ’hongersnood’ ZANU PF se beheer oor die samelewing effektief verleng het - maar ons toon ook aan hoe ’gewone mense’ teruggeveg het teen president Robert Mugabe se ’groot manne/elite’ deur ’kleingrane’ te verbou en te verbruik.